Integrated assessments of climate change policy: Intergenerational equity and discounting - Ferenc L. Toth (Fondazione Eni Enrico Mattei (FEEM), 1999)
One of the key decisions that economists working on integrated studies of climate change face is the selection of the method of accounting for damages resulting from possible climate change across a long temporal scale and the method for the intertemporal comparison of the costs associated with possible greenhouse gas abatement strategies. Sensitivity tests show that the method applied and the resulting discount rate has a major impact on the optimal climate strategy. The paper provides a short review of the various techniques that have been proposed and applied in various integrated models of climate change. The underlying problem is the following dilemma. One can attempt to be consistent with the economic theory and empirical observations, but in this case the derived discount rate will be on the order of 5 to 8%. As a result, even possibly significant damages from climate change turn out to be negligible when considered at their present value. The artificially low discount rate based on ethical reasoning, on the other hand, makes our climate-related decisions and resource allocations inconsistent with the majority of other public policy decisions.
Keywords: C61; D61; E13; Q25; 330; Integrated assessments; Climate change; Intergenerational equity; Discounting; Klimaschutz; Wirkungsanalyse; Abzinsung; Overlapping Generations; Theorie